2010
DOI: 10.1093/molbev/msq086
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of Expression and Evolution of Intronless and Intron-Containing Mammalian Genes

Abstract: Comparison of expression levels and breadth and evolutionary rates of intronless and intron-containing mammalian genes shows that intronless genes are expressed at lower levels, tend to be tissue specific, and evolve significantly faster than spliced genes. By contrast, monomorphic spliced genes that are not subject to detectable alternative splicing and polymorphic alternatively spliced genes show similar statistically indistinguishable patterns of expression and evolution. Alternative splicing is most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 29 publications
9
100
0
Order By: Relevance
“…The low number of introns has also been noted in putative lncRNAs obtained in some but not all large-scale studies (Ravasi et al 2006;Guttman et al 2010;Ørom et al 2010). It has been shown that at least among protein-coding RNAs, the intron-less transcripts as a group have a lower transcriptional expression level and a more tissue-specific expression pattern compared with spliced messages (Shabalina et al 2010). Furthermore, the intron- less mRNAs were evolutionarily younger, showed lower interspecies sequence conservation, and seemed to code disproportionately for regulatory proteins (Shabalina et al 2010).…”
Section: Architecture Of Lncrna Transcriptsmentioning
confidence: 90%
See 2 more Smart Citations
“…The low number of introns has also been noted in putative lncRNAs obtained in some but not all large-scale studies (Ravasi et al 2006;Guttman et al 2010;Ørom et al 2010). It has been shown that at least among protein-coding RNAs, the intron-less transcripts as a group have a lower transcriptional expression level and a more tissue-specific expression pattern compared with spliced messages (Shabalina et al 2010). Furthermore, the intron- less mRNAs were evolutionarily younger, showed lower interspecies sequence conservation, and seemed to code disproportionately for regulatory proteins (Shabalina et al 2010).…”
Section: Architecture Of Lncrna Transcriptsmentioning
confidence: 90%
“…To elucidate features unique to this class of functional RNAs, a parallel analysis was performed on a database containing all human protein-coding genes. The results revealed the presence of several common sequence features among lncRNAs, including the paucity or absence of introns and the low GC content, which could at least partly explain the nuclear localization and low expression levels observed in many lncRNAs (Kelly and Corbett 2009;Shabalina et al 2010). A detailed analysis of their proteincoding capacity indicated that while the lncRNAs do contain short ORFs, their poor start codon context makes efficient translation unlikely.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been suggested that older duplicates undergo more alternative splicing than recent duplicates (Kopelman et al 2005;Su et al 2006;Shabalina et al 2010). We dated duplication events using tree reconciliation from Ensembl Compara (Vilella et al 2009), which allows higher resolution than previously used methods.…”
Section: Age Mattersmentioning
confidence: 99%
“…A lthough the vast majority of pre-mRNAs in higher eukaryotes contain introns, 5% of human protein-coding genes do not contain introns (1). However, these naturally intronless mRNAs encode proteins of critical importance, including the histones, the c-Jun proto-oncoprotein, and the antiviral IFN proteins.…”
mentioning
confidence: 99%